Wearing Face Mask and Occurrence of Dry Mouth - Ismalayani Ismalayani (Humanistic Network for Science and Technology (HNST), 2022)
In Covid-19 pandemic era, wearing of face mask has become a necessity, not only in hospitals but also in society. Although wearing face mask can reduce the risk of transmitting SARS-CoV-2 infection, it has certain detrimental effects. One of the side effects to pay attention to is the wearer's oral health, namely mask mouth or xerostomia or what is commonly referred to as dry mouth syndrome. This study aim was to determine the effect of wearing face masks on the occurrence of dry mouth. This cross sectional study was conducted in February 2021. Sample consisted of 82 people aged 18-45 years in Kemuning Subdistrict, Sekip Jaya, Palembang, South Sumatera who were taken by simple random sampling. Data was obtained from filling out online questionnaires and analyzed using the Chi-square test with the significance interval 95%. Respondents who wear cloth mask, medical mask, and N95 mask and experiencing dry mouth as many as 95.4%, 80%, and 80%, respectively. Dry mouth were occur on 50% respondents who wear face mask <1 hour, 100% respondents who wear face mask for 1-2 hours and 2-4 hours, 55.6% respondens who wear face mask for 5-6 hours and 83.9% respondents who wear face mask >6 hours. There was no significant association between type of face mask with occurrence of dry mouth (p>0.05). Otherwise, there was significant association between duration wearing face mask with occurrence of dry mouth (p<0.05). It can be concluded that wearing face mask can promote the dry mouth. Keywords: SARS-CoV-2; mask; dry mouth